Peer-to-Peer Lending: Bridging the Financial Inclusion Gap by Leveraging Technology - Bhattacharya, Anirban; Chopra, Anmol (Indian Journal of Finance, 2019)
With Indian banks grappling with asset quality issues leading to capital-constrained low credit growth, there remains a large gap between credit demand and supply for 'retail' individual borrowers and small businesses under the MSE sector. Alternate financing channels identified this void and have started making their presence felt in the recent years. Within the alternate financing options, peer-to-peer (P2P) lending platforms are best suited to cater to the credit needs of retail customers and micro and small enterprises (MSEs). This paper tried to estimate the credit demand for six major segments (across 'retail' sector and MSEs) and compared it with the trend in credit supply in order to estimate the demand-supply gap. Annual data from 2004 to 2016 was used for the forecast as reliable data for some of the above variables is not available after that. The credit demand was forecasted at the end of fiscal year (FY) 2022. Subsequently, the current P2P landscape in India was explored along with the regulatory structure in place. Whether P2P platforms will be able to fill the credit gap left by traditional banking channels or not will depend on how different stakeholders, that is, leading industry players and banking and capital market regulators provide a nurturing environment to the sector. With active participation from key stakeholders, P2P lending has the potential to create a sustainable, complementary market to the traditional credit intermediation instruments.